2020
DOI: 10.3389/fimmu.2020.01607
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Characteristics and Associated Factors of Infectious Complications in Bullous Pemphigoid

Abstract: Objectives:The clinical outcome of bullous pemphigoid appears worse in patients with infectious complications, and assessment of the prevalence and risk factors of infectious complications could be necessary to plan preventative strategies and to instruct the treatment plans. We sought to determine the risk factors of infection and compare associated factors in inpatients and outpatients with different system infections. Design: This is a single-centered retrospective study on the medical records of 252 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 35 publications
(49 reference statements)
5
20
0
Order By: Relevance
“…Furthermore, it will be interesting to investigate whether there is a significantly elevated expression of the cytokines in the perilesional and lesional skin in future work. Nevertheless, our study presented a series of patients matched with a group of healthy subjects and whose clinical features align with those previously reported series, including characteristics such as age, sex, mucosal involvement, corticosteroid dose, and relapse rate (28,36,51,(59)(60)(61). Remarkably, our studies have identified that BP is associated with IL-13 gene polymorphism and an increased IL-13 in the peripheral blood.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, it will be interesting to investigate whether there is a significantly elevated expression of the cytokines in the perilesional and lesional skin in future work. Nevertheless, our study presented a series of patients matched with a group of healthy subjects and whose clinical features align with those previously reported series, including characteristics such as age, sex, mucosal involvement, corticosteroid dose, and relapse rate (28,36,51,(59)(60)(61). Remarkably, our studies have identified that BP is associated with IL-13 gene polymorphism and an increased IL-13 in the peripheral blood.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, several lines of evidence have shown that IL-4 and IL-13 could impair skin barrier function by suppressing the expression of tight junction proteins, filaggrin, loricrin, and involucrin (46)(47)(48). Other groups and we have previously shown a high incidence rate of local skin or systemic infections in BP (49)(50)(51). It will be interesting to investigate in the future whether these cytokines are involved in infections in BP patients.…”
Section: Discussionmentioning
confidence: 83%
“…19,20 The most common infections in bullous pemphigoid patients are found in the skin and mucosa. 21 In our cohort, all detected skin infections were staphylococcal and required systemic antibiotics. Of these, three (3.3%) patients died of sepsis with methicillin-resistant Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 73%
“…9 Infections like cutaneous and respiratory infections are predominant contributor of BP death. 10,11 Thus, cooperation between dermatologist and primary care physicians and other specialties are essential for BP patients. However, our knowledge about the epidemiology of BP is still limited.…”
Section: Introductionmentioning
confidence: 99%